Frequency of ultrasound diagnosis of canine hydrops fetalis and associated variables in a veterinary clinic in Lima, Peru - Cuesta T., Gabriela (2023)
The aim of this study was to determine the frequency of ultrasound diagnosis of pregnancy with hydrops fetalis in bitches and its association with dam's race, age, parity, litter size and year of diagnosis. Ultrasound reports and stored images of bitches treated at the Ultrasound Service of the Small Animal Clinic of the Faculty of Veterinary Medicine, Universidad Nacional Mayor de San Marcos from 2013 to 2017 were reviewed. The "ultrasound patterns of canine foetal hydrops presentation" were characterized: Subcutaneous oedema, Pleural effusion, Ascites, Subcutaneous oedema and pleural effusion, Subcutaneous oedema and ascites, Pleural effusion and ascites, and Subcutaneous oedema with pleural effusion and ascites. The frequency of foetal hydrops was 11.6% (109/938) and affected 4.92% (233/4740) of the foetuses. The association was greater in defined breeds (12.5%), aged 25 months to 4 years (14%) and up to 2 years (12.7%), in multiparous bitches (15.9%), in gestations between 6 to 8 foetuses (16.4 %) and with more than 8 foetuses (18.4%), and in 2016 (10.6%) and 2017 (22%). The English Bulldog (37.3%) weas the breed with the highest frequency of hydrops fetalis. All echography patterns of foetal hydrops were found, being subcutaneous oedema the most frequent, both in pregnancies (8.8%) and in foetuses (81.55%).